Association of Phase Angle, but Not Inflammation and Overhydration, With Physical Function in Peritoneal Dialysis Patients - Silva, Vanessa Mota; Silva, Maryanne Zilli Canedo; Vogt, Barbara Perez; Reis, Nayrana Soares Carmo; Costa, Fabiana Lourenço; Dorna, Mariana Souza; Minicucci, Marcos Ferreira; Caramori, Jacqueline Costa Teixeira (Frontiers in Nutrition, 2021)
Introduction: Muscle mass depletion, overhydration and inflammatory state have been related to impaired physical function in chronic kidney disease patients. The relationship between bioelectrical impedance analysis (BIA) parameters, such as hydration status and phase angle (PhA), with physical function in peritoneal dialysis (PD) is still not well established. Therefore, the objective was to evaluate the association of BIA parameters (overhydration index and PhA) and inflammatory markers with physical function in patients on PD. Methods: Cross-sectional study enrolling PD patients. Multifrequency BIA was performed to obtain overhydration index and PhA. The Short Physical Performance Battery (SPPB) test battery was applied to assess physical function. The time to complete the 4-meter gait test and sit-to-stand test were also considered for physical function assessment. The inflammatory markers tumor necrosis factor-alpha and C-reactive protein levels were determined. Multiple linear regression models were performed, with the physical function variables as dependent variables, adjusted for age, diabetes and sex. Results: 49 PD patients were enrolled, 53.1% (n=26) women, mean age 55.5 ± 16.3 years. There were significant correlations between PhA and SPPB (r=0.550, p<0.001), time of 4-meter gait test (r= -0.613, p<0.001) and sit-to-stand test and (r= -0.547, p<0.001). Overhydration index was significantly correlated with SPPB, 4-meter gait test (r=0.339, p=0.017) and sit-to-stand test (r=0.335, p= 0.019). Inflammatory markers were not significantly correlated with physical function parameters. In the multiple linear regression analysis, PhA was associated with physical function parameters, even after adjustments. Overhydration index was associated with all physical function tests only in the models with no adjustments. Conclusion: PhA was independently associated with physical function in PD patients. Inflammatory markers and overhydration index were not associated with physical function.